Conflict Between Human and Asian Elephant in the Buffer Zone of Parsa-Chitwan Complex, Nepal - Shah, Rubi; Karki, Jhamak Bahadur (Journal of Agriculture and Forestry University, 2025)
Asian elephants are the largest land mammals, faced significant threats because of the loss and fragmentation of their natural habitat mainly due to the cropping patterns near the protected areas contributing human-wildlife conflict. The aim of this study was to find out conflict between Human and wild elephant in buffer zone of Parsa and Chitwan National Parks. Social survey with a semi structured questionnaire with Fifty-two elephant affected respondents, three focus group (6-8 people) in each discussion as per the agreed discussion guides and direct field observation were done. The elephants were attracted by agriculture crop near the park. Crop damage predominantly occurred at night, especially during the ripening periods of paddy and maize from June to November. Elephants, initially led by a solitary male, enter after sunset and evaluate the conditions for foraging the crops. Later, a group of 2-3 elephants, including the male, engaged in nocturnal crop raiding before departing by dawn. Crop raiding incidents peaked during this time, aligning with the harvesting seasons for both winter and summer paddy. The damage increased notably during the Paddy season, followed by the Maize season and other crops. Villagers employed active methods like noise making and lighting, while some locals adopted passive strategies such as cultivating alternative crops and harvesting maize prematurely to minimize damage. Villagers prioritized chasing, sound, and stone pelting as effective deterrents against elephant intrusion. These observations underline the seasonal and crop-specific nature of elephant-induced crop damage, and the varied strategies used to mitigate these conflicts.